A systematic literature review on performance of social enterprises - Aamir Hussain; Aznor Ahmad; Shahin Mia (Cogent Economics & Finance, 2023)
Assessing the performance of social enterprises is gaining popularity in the academic world in recent years. However, different studies focused on different dimensions of performance evaluation. For instance, some studies measured social performance of the social enterprises while others paid attention to financial performance. Consequently, it creates a research gap lacking a complete picture of performance evaluation of social enterprises globally. Insufficient performance evaluation, limited assessment methods, and a lack of systematic thinking are the causes of this research gap. Therefore, this study aims to carry out a systematic literature review to provide a complete picture on performance of social enterprises. Preferred Reporting Items for Systematic Reviews and Meta-Analyses were used to generate a systematic literature review. The study reviewed systematically 35 scholarly articles that focused on social and financial performance of social enterprises. The findings indicate that social enterprises have strong financial and social support and can incorporate different types of resources and goals. It is also reported that performance, which is frequently linked with specific external and internal assistance are essential variables in enabling social enterprises to grow. The study findings might provide a new insight and understanding to fulfil the research gap in this area.
Keywords: 330; financial performance; social enterprise; social performance; systematic literature review